2021
DOI: 10.1186/s13031-021-00421-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of social capital in women’s sexual and reproductive health and rights in humanitarian settings: a systematic review of qualitative studies

Abstract: Background Social capital is an important social determinant of women’s sexual and reproductive health and rights. Little research has been conducted to understand the role of social capital in women’s sexual and reproductive health and how this can be harnessed to improve health in humanitarian settings. We synthesised the evidence to examine the nexus of women’s sexual and reproductive health and rights and social capital in humanitarian contexts. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 55 publications
2
9
0
1
Order By: Relevance
“…Sexual violence roots in social structures, frameworks, and policies, and their weakness can lead to pre- and postdisaster sexual violence ( 60 ). A study has stated that in the event of a disaster, the society should support and protect people, especially women and girls, which requires years of planning in the community before disasters ( 61 , 62 ), which is in line with the results of the present study. To properly manage sexual violence, it is necessary to identify the cultural, socioeconomical roots and social norms and consider them in policies ( 61 , 63 ) and consider the important role of policymakers in preparing and providing appropriate responses to sexual violence in disasters ( 11 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Sexual violence roots in social structures, frameworks, and policies, and their weakness can lead to pre- and postdisaster sexual violence ( 60 ). A study has stated that in the event of a disaster, the society should support and protect people, especially women and girls, which requires years of planning in the community before disasters ( 61 , 62 ), which is in line with the results of the present study. To properly manage sexual violence, it is necessary to identify the cultural, socioeconomical roots and social norms and consider them in policies ( 61 , 63 ) and consider the important role of policymakers in preparing and providing appropriate responses to sexual violence in disasters ( 11 ).…”
Section: Discussionsupporting
confidence: 89%
“…Researchers have found that comprehensive planning is required to be in line with the culture of the people in affected areas and provide appropriate and timely services and protect human rights. Therefore, strong and sustainable preparedness programs are needed to respond to the needs of sexual violence victims ( 62 , 75 ). Developing a contingency plan will also help to prevent disasters and their consequences.…”
Section: Discussionmentioning
confidence: 99%
“…A clear and in-depth understanding of regulations guiding the SRHR of these populations by both livedexperience insights gained directly from inhabitants in addition to the insight provided by service providers is also paramount to integrating both perspectives to better understand how to address these continuing gaps that prevent women and girls from achieving optimal SRH [5,14]. Therefore, highly active multi-sectoral collaboration is required to provide high-quality and accountable services [49] and to recognize that SRHR constitutes a basic human right that does not need to be violated [22,50].…”
Section: Discussionmentioning
confidence: 99%
“…The study nds that social capital is signi cantly related to a variety of positive health outcomes (19). Communities with higher social capital may have better access to sexual education and healthcare services, potentially leading to improved psychosexual health outcomes (20). There is a connection between social capital and psychological well-being.…”
Section: Introductionmentioning
confidence: 93%